INVERTER CIRCUIT - FURUKAWA KIMIHIKO (1999)
PROBLEM TO BE SOLVED: To precisely detect a direct current contained in an output current of an inverter main circuit with a simple constitution so as to control the direct current. SOLUTION: This circuit is constituted of an inverter main circuit for converting D.C. power to A.C. power to be output to a D.C. output line 7, and an inverter control circuit for controlling operation of the inverter main circuit. In an inverter circuit having a control function to control to zero a direct current flowing in the D.C. output line 7, the inverter control circuit is provided with a current control circuit 13 containing a current sensor 8 fitted to the line 7, and a highly precise detection circuit 14 containing a shunt resistance 9 interposed in the line 7. The detection circuit 14 detects a direct current based on voltages of both ends in the shunt resistance 9 and converts a detected value into one or plural binary digits of digital values to be fed to the current control circuit 13, and the control circuit 13 receives supply of the digital values to correct a zero point of the current sensor 8.